2007
DOI: 10.2134/agronj2006.0360
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiological Yield Components of Maize Hybrids with Contrasting Maturity

Abstract: The length of the growing cycle is one of the most important traits determining hybrid adaptability to the environment. The objective of this work was to study the development, dry matter accumulation, grain yield, harvest index, and sink-source relationship of 11 maize (Zea mays L.) hybrids with contrasting maturity. The durations of the cycle from emergence to flowering varied from 537 to 781 growing degree days and from emergence to physiological maturity from 1221 to 1656°Cd. Cumulative biomass from emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 31 publications
2
31
0
Order By: Relevance
“…Kernel weight was similar for the 95‐ and 101‐d RM hybrids and averaged 8% higher than that for the 105‐d RM hybrid (Table 3); however, the 105‐d RM hybrid averaged 19% more kernels per square meter than the 95‐ and 101‐d RM hybrids, which contributed to it having the highest yield. Capristo et al (2007) also reported that early‐RM hybrids had lower yield than late‐RM hybrids due to fewer kernels. Because the grain‐filling period of the 105‐d RM hybrid occurred slightly later and for a longer duration than for the 95‐ and 101‐d RM hybrids (data not shown), below‐average air temperatures in August of 2009 and September of 2010 (Table 1) may have prevented the 105‐d RM hybrid from having a kernel weight as high as the 95‐ and 101‐d RM hybrids.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Kernel weight was similar for the 95‐ and 101‐d RM hybrids and averaged 8% higher than that for the 105‐d RM hybrid (Table 3); however, the 105‐d RM hybrid averaged 19% more kernels per square meter than the 95‐ and 101‐d RM hybrids, which contributed to it having the highest yield. Capristo et al (2007) also reported that early‐RM hybrids had lower yield than late‐RM hybrids due to fewer kernels. Because the grain‐filling period of the 105‐d RM hybrid occurred slightly later and for a longer duration than for the 95‐ and 101‐d RM hybrids (data not shown), below‐average air temperatures in August of 2009 and September of 2010 (Table 1) may have prevented the 105‐d RM hybrid from having a kernel weight as high as the 95‐ and 101‐d RM hybrids.…”
Section: Resultsmentioning
confidence: 97%
“…In these trials, grain moisture at harvest in the 103‐ to 107‐d RM group averaged 17 and 30 g kg −1 higher than that in the 98‐ to 102‐ and 93‐ to 97‐d RM groups, respectively. Capristo et al (2007) determined that the early‐RM hybrids had lower yield due to a reduction in kernel number and were more sink limited than late‐RM hybrids. When both grain yield and moisture at harvest are considered, however, the net return with late‐maturity hybrids is often only slightly higher than with early‐maturity hybrids due to the additional costs for grain drying (Lauer et al, 1999).…”
mentioning
confidence: 99%
“…, 1993). The OHU model is primarily used to predict the suitability of a climate for growing specific maize cultivars or vice‐versa (Kwabiah, 2003; Capristo et al. , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Yield per plant decreases as crowding stress increases. Yield reduction is mostly due to lower ear numbers (barrenness) (Hashemi et al 2005), fewer kernels per ear (Capristo et al 2007), lower kernel weight (Monneveux et al 2005) or a combination of these components. Grain yield per unit area is the product of grain yield per plant and planting density.…”
Section: Introductionmentioning
confidence: 99%